A novel scheme to enhance both electromagnetic wave transmission and compressive properties of PMI foam sandwich structures. (1st December 2021) - Yan, Leilei; He, Zhiheng; Jiang, Wei; Cheng, Linhao; Ma, Hua; Zheng, Xitao
Highlights: A novel antireflection PMI foam sandwich structure based on SSPPs structure was proposed. The proposed structure has broadband EM wave transmission in X and Ku band under the oblique incidence. Its compressive strength and energy absorption were dramatically increased by 72% and 60% respectively. Abstract: Aimed to enhance electromagnetic (EM) wave transmission and compressive properties of sandwich structures with FR-4 face sheets and the polymethacrylimide (PMI) foam core, a kind of spoof surface plasmon polaritons (SSPPs) structure realized by gradient metal wire arrays was proposed and inserted into the PMI foam core to form a novel antireflection sandwich structure. The transmission performances under normal and oblique incidence were studied by simulation and experimental methods. The results showed that this sandwich structure can achieve a broadband enhanced transmission in X and Ku bands. The enhanced transmission mechanism was suggested to be the effect of the inserted SSPPs structure which changed the transmission path of EM waves in a local area, increased the interface refraction angle and greatly suppressed reflection of each interface. In addition, compressive properties of the sandwich structures were studied experimentally, and the results showed that compared with normal PMI foam sandwich structure, the compressive strength and the energy absorption per unit volume of the antireflection sandwich structure were increased by 72% and 60%. The proposed antireflection sandwich structure is more effective and competitive in load bearing and EM wave transmission applications than traditional structures.